1971
DOI: 10.1128/jb.106.3.876-881.1971
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Composition of Thermophilic, Mesophilic, and Psychrophilic Clostridia

Abstract: The fatty acid composition of two thermophilic anaerobes was determined, and the results were compared with those from a mesophilic and a psychrophilic anaerobe. Notable differences were that the thermophiles contained a higher content of saturated straight- and branched-chain fatty acids, and, of the latter, iso C 15 was the predominant type. The mesophile and psychrophile were characterized by having a higher percentage of unsaturated fatty acids. An unidentified fatty acid, present i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
17
0

Year Published

1972
1972
2006
2006

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(22 citation statements)
references
References 20 publications
5
17
0
Order By: Relevance
“…the study of CIostridium spp. by Chan et aL [25]. Even this approach has its problems and in this example the thermophilic, but not the mesophilic and psychrophilic spp., wcrc found to contain branched-chain fatty acids.…”
Section: Comparison Of Psychrophiles and Thermophilesmentioning
confidence: 90%
“…the study of CIostridium spp. by Chan et aL [25]. Even this approach has its problems and in this example the thermophilic, but not the mesophilic and psychrophilic spp., wcrc found to contain branched-chain fatty acids.…”
Section: Comparison Of Psychrophiles and Thermophilesmentioning
confidence: 90%
“…Since these organisms represent totally unrelated genera, it has at times been difficult to determine whether observed differences are due to growth temperature or simply to intergeneric variation. Recently, several studies comparing mesophilic and thermophilic species from the same genus have been made, thus eliminating at least part of the problem (4,8,17,19).…”
mentioning
confidence: 99%
“…Obligate psychrophilic species of clostridria have been characterized, and these have been shown to be obligate anaerobes (18). Comparison of the fatty acid compositions of psychrophilic and thermophilic clostridia have further shown that the psychrophiles have a high percentage of unsaturated fatty acids (7). The differences between the eucaryotic and procaryotic systems may thus be related in the ability of the latter group to synthesize unsaturated fatty acids anaerobically (13), a property not shared by eucaryotic microorganisms.…”
mentioning
confidence: 99%